Mach-Zehnder interferometer - Yahya, Esmael H. M. (2007)
Beam propagation method (BPM) was used to study 2x2 Mach-Zehnder interferometer switch with electro-optical effects in titanium diffused lithium niobate based directional coupler was used to develop the design. This design is capable of de-multiplexing the wavelength1300nm. This project intends to design high performance NxN electro-optic switch. This optical device is widely used in optical network, especially in the optical link of fiber-to-the-home (FTTH). The design is carried out using BPM_CAD, which is a very powerful and user-friendly optics waveguides modeling method as it core element. Research on optical waveguide switching using directional coupler (DC) and Mach-Zehnder interferometer (MZI) has been going on and already created great interest among the researchers. There are different types of material being used in much different way apart from the most common electro-optic materials such as lithium niobate. Recently, the study was also confined to the use of silica on silicon technology considering that the cost of the technology. Other non-linear-optic materials such as polymers have been embedded into part of the silica waveguide.